A performance analysis of a power system and its improvement measures : the case of Bangladesh - Islam, Md. Naimul; Edelman, Davjd J.; Bhattacharya, Sribas C.; Supachart C.; The Government of Japan (Bangkok : Asian Institute of Technology, 1992)
With the increase in p1ices of fuel, the increasing demand for electricity with the growing population of Bangladesh has forced power engineers to think seriously about a power system perfo1mance assessment. In the present study, the perfomrnnce analysis of the power system and its possible improvement measures was carried out at the unit, pl1mt and utility levels of Bangladesh through an integrated approach. The segmented approach of lineaJ programming was used. to detennine an opt.ima1 generation -mix at minimum production cost. This yielded a 16.4 7 % reduet:ion in product.ion cost. A retrospective analysis of plant productivity with respect to labor and stock of capital utilization was then conducted to measure how effectively the fi xed assets and labor were employed by the Bangladesh Power Development Board (BPDB) in the power production and distribution process. Finally, some technical ratios/indicators such as plant load factor, heat rate, availability fact.or, forced outage rate, auxrnary consumption, system losses, and system reliabiJity,etc. were considered for pe1fo1mance assessment and analyzed critically. A se1ies of practical steps were conducted to reduce trammission and distribution losses and to increase the them1al efficiency of sorne plants (in some cases, plant capacity). A partial cost-benefit analysis was also done to assess the economic value of the study's recommendations.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Plant performance -- Bangladesh; Electric power-plants -- Bangladesh -- Efficiency